The use of enteral access for continuous delivery of levodopa-carbidopa in patients with advanced Parkinson's disease. Issue 1 (February 2017) - Cheron, Julian; Deviere, Jacques; Supiot, Frederic; Ballarin, Asuncion; Eisendrath, Pierre; Toussaint, Emmanuel; Huberty, Vincent; Musala, Carmen; Blero, Daniel; Lemmers, Arnaud; Van Gossum, André; Arvanitakis, Marianna
Background: Continuous delivery to the jejunum of levodopa-carbidopa is a promising therapy in patients with advanced Parkinson's disease, as it reduces motor fluctuation. Percutaneous endoscopic gastrostomy and jejunal tube (PEG-J) placement is a suitable option for this. However, studies focused in PEG-J management are lacking. Objectives: We report our experience regarding this technique, including technical success, adverse events and outcomes, in patients with advanced Parkinson's disease. Methods: Twenty-seven advanced Parkinson's disease patients (17 men, median age: 64 years, median disease duration: 11 years) were included in a retrospective study from June 2007 to April 2015. The median follow-up period was 48 months (1–96). Results: No adverse events were noted during and after nasojejunal tube insertion (to assess treatment efficacy). After a good therapeutic response, a PEG-J was placed successfully in all patients. The PEG tube was inserted according to Ponsky's method. The jejunal extension was inserted during the same procedure in all patients. Twelve patients (44%) experienced severe adverse events related to the PEG-J insertion, which occurred after a median follow-up of 15.5 months. Endoscopy was the main treatment modality. Patients who experienced severe adverse events had a higher comorbidity score ( p  = 0.011) but were not older ( p  = 0.941) than patients who did not. Conclusions: While all patients responded well to levodopa-carbidopa regarding neurological outcomes, gastro-intestinal severe adverse events were frequent and related to comorbidities. Endoscopic treatment is the cornerstone for management of PEG-J related events. In conclusion, clinicians and endoscopists, as well as patients, should be fully informed of procedure-related adverse events and patients should be followed in centres experienced in their management.